PEMBUATAN DAN PENYEDIAAN MATERI LITERASI BUDAYA DI SPOT WISATA POJOK HASTA KARYA PENTUNGAN SARI - Setiawati, Eti; Rizal, Maulfi Syaiful; Sukmawan, Sony; Zakiyah, Millatuz (Faculty of Cultural Studies, Universitas Brawijaya, 2023)
Enhancing and promoting Toyomarto's unique cultural products, particularly in the form of cultural literacy, has so far received little attention from the community, even though this could be utilized as a tourist attraction and has the potential to attract tourists. Based on this, Toyomarto Village, as a tourist village, is worthy of developing the idea of cultural literacy to be showcased at the Pentungan Sari craft corner tourist spot. The objective of this community service activity is to provide an opportunity for the Toyomarto community to revive the village's small and medium enterprises (SMEs) regarding Toyomarto's signature products, enhance and promote Toyomarto's unique cultural products, particularly through cultural literacy initiatives, thereby transforming them into tourist attractions and attracting visitors. Additionally, it aims to deepen visitors' and the community's understanding of cultural literacy by highlighting the diverse potential and traditions surrounding Pentungan Sari, as well as to improve cultural literacy and educational facilities for local residents, particularly students at the kindergarten to junior high school levels in Toyomarto Village. The benefits gained from this community service include: (1) economic benefits that can open up opportunities for the Toyomarto community to revive village MSMEs regarding Toyomarto's signature products. With the reestablishment of local MSMEs, it will add value to the community's economy, thereby enabling the community to become independent and prosperous. (2) Cultural benefits, which are expected to promote Toyomarto's unique cultural products, from cultural literacy materials to tangible products, thereby becoming an attractive destination for tourists, (3) Economic and strategic benefits for the image of the Toyomarto village government, which is expected to serve as an alternative for the broader community to promote literacy.